(untitled) (MAUSAM, 1980)
Measurements of soil heat flux were made over bare black cotton soil at Pune in the period June 1976 to February 1977, using a soil heat flux plate. Hourly values of soil heat flux from 00 to 24 LAT are presented for selected days typical of the monsoon, post-monsoon and winter seasons. The diurnal variation is generally characterised by a cross-over from negative to positive values at 07 hr, occurrence of maximum around noon and return to negative values between 16 and 18 hr. The effects of rainfall, cloudiness and soil moisture on the soil heat flux are discussed.